MODIFIED RELEASE DRUG DELIVERY SYSTEM: CONCEPT AND SYSTEM DESIGN OF RATE-CONTROLLED DRUG DELIVERY SYSTEM - Ankit Singh; Dakshina Gupta; Saurabh Singh (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Purpose-Among the various routes of drug delivery oral route is most preferred route. But conventional dosage form offers few limitations which could be resolved by modifying the existing dosage form. Sustained and controlled drug delivery system helps in maintaining of constant plasma drug concentration and retards the release rate of drug thereby extending the duration of action. There are various formulation strategies for sustained release tablets among which matrix tablet serves as an important tool. Hence the problem like poor patient compliance, multiple dosing, see-saw fluctuations can be easily minimized. Matrix tablets can be formulated by either direct compression or wet granulation method by using a variety of hydrophilic or hydrophobic polymers. The rate of drug release from the matrix is primarily governed by rate and extent of water penetration, swelling of polymer, dissolution and diffusion of drug. Conclusion- Thus, sustained release matrix tablet can offer better patient compliance and could be quite helpful in treatment of chronic diseases. The present article concentrates on oral sustained release tablets with a special emphasis on matrix tablet.